Preliminary study of the psychometric properties of the scale for the identification of violence and the scope where it is presented for children from 8 to 12 years old - Parraguez Burga, Nisi (2019)
Objective: The objective of this study was to construct an instrument based on psychometricproperties, in order to identify physical, psychological and sexual violence in the home, street andschool settings. Material and Methods: The design of the research is quantitative, non-experimentaldesign, cross-section and psychometric because it sought to establish the validity and reliability of thequestionnaire designed for this study. Results: In the first stage, the conceptual delimitation of theconstruct was carried out and the preliminary instrument (63 items) was elaborated based on a reviewof the literature on violence in childhood. The quality of the items was evaluated through 6 experts in thearea using the coefficient of validity V of Aiken. In the second stage, a pilot sample of 401 students wasconsidered in two educational institutions, where the selection of items was performed based on threestatistical criteria. Then, the exploratory factor analysis was carried out in order to rigorously analyzethe theoretical and dimensional nature of the construct. In addition, the Cronbach alpha coefficient wasobtained for the sub-dimensions, and global scale. Conclusions: The final scale was composed by 38items that form 3 dimensions and 3 sub dimensions that have adequate levels of reliability and validity